Up‐Regulation of Transient Receptor Potential Melastatin 6 Channel Expression by Tumor Necrosis Factor‐α in the Presence of Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor. Issue 10 (25th April 2017) - Furukawa, Chisa; Fujii, Naoko; Manabe, Aya; Matsunaga, Toshiyuki; Endo, Satoshi; Hasegawa, Hajime; Ito, Yoshinori; Yamaguchi, Masahiko; Yamazaki, Yasuhiro; Ikari, Akira
Abstract : Anti‐epidermal growth factor receptor (EGFR) drugs such as erlotinib and gefitinib cause a side effect of hypomagnesemia, but chemotherapy to treat this has not yet been developed. The transient receptor potential melastatin 6 (TRPM6) channel is involved in the reabsorption of Mg 2+ in the renal tubule. We reported previously that the expression of TRPM6 is up‐regulated by epidermal growth factor (EGF) in renal tubular epithelial NRK‐52E and HEK293 cells. EGF‐induced elevation of TRPM6 expression was inhibited by erlotinib, gefitinib, and lapatinib. We found that tumor necrosis factor‐α (TNF‐α) increases TRPM6 expression in the presence of erlotinib. Therefore, we investigated what molecules are involved in the up‐regulation of TRPM6 expression by TNF‐α. EGF increased the levels of phosphorylated extracellular signal‐regulated kinase 1 and 2 (p‐ERK1/2), which were inhibited by erlotinib. TNF‐α did not change p‐ERK1/2 levels, but increased the phosphorylation and nuclear localization of nuclear factor‐κB (NF‐κB), which were blocked by the NF‐κB inhibitors BAY 11–7082 and pyrrolidinedithiocarbamate ammonium. Similarly, luciferase reporter activity of human TRPM6 was increased by TNF‐α, which was blocked by NF‐κB inhibitors, and was inhibited by a mutation in the κB‐binding site in the proximal region of the TRPM6 promoter. A chromatin immunoprecipitation assay revealed that NF‐κB binds to the κB‐binding site, which was blocked by NF‐κB inhibitors. In the presence of erlotinib, TNF‐α increased Mg 2+ influx, which was blocked by NF‐κB inhibitors. These results suggest that TNF‐α reverses the reduction in Mg 2+ reabsorption caused by anti‐EGFR drugs. J. Cell. Physiol. 232: 2841–2850, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Tumor necrosis factor‐α (TNF‐α) increases TRPM6 expression in the presence of anti‐epidermal growth factor receptor drug, erlotinib. TNF‐α did not change p‐ERκ1/2 levels, but increased the phosphorylation and nuclear localization of nuclear factor‐κB (NF‐κB), which were blocked by the NF‐κB inhibitors. In the presence of erlotinib, TNF‐α increased Mg 2+ influx, which was blocked by NF‐κB inhibitors.